2017
DOI: 10.4236/ojog.2017.75052
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrical and Perinatal Outcomes of Teenage Pregnant Women Attending a Secondary Hospital in Hyderabad

Abstract: Objective: To evaluate the frequency of adverse maternal and perinatal outcomes in teenage pregnancies at secondary hospital Hyderabad. Methods: Retrospective record review was conducted between January 2012 to January 2016. Total No. of deliveries was 15,395 out of which No. of teenage was 452. Results: Rate of teenage pregnancy in our hospital during study period was 2.93%. Majority of women were uneducated. Teenage mother more likely to develop pregnancy induced hypertension 19.5%, frequency of mild, modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Teenage pregnancy is greatly associated with adverse pregnancy outcomes like obstructed labor, pre-eclampsia, anemia, operative deliveries, puerperal endometritis, postpartum hemorrhage, low birth weight, preterm delivery, and perinatal death [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Teenage pregnancy is greatly associated with adverse pregnancy outcomes like obstructed labor, pre-eclampsia, anemia, operative deliveries, puerperal endometritis, postpartum hemorrhage, low birth weight, preterm delivery, and perinatal death [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been associated with metabolic consequences, 35 resulting in poor growth and development, and affects the quality of life. 36 We need to identify the most feasible dietary interventions, including behavioural change communication interventions for pregnant adolescents, aimed at preventing adverse neonatal and infant outcomes. 37 …”
Section: Discussionmentioning
confidence: 99%
“…It has also been associated with metabolic consequences, 35 resulting in poor growth and development, and affects the quality of life. 36 We need to identify the most feasible dietary interventions, including behavioural change communication interventions for pregnant adolescents, aimed at preventing adverse neonatal and infant outcomes. 37 There are similarities between some of the barriers to good dietary practice expressed by healthcare providers in this study and those described by Abas et al on Barriers to Optimal Maternal Nutrition in the Somali Region, Eastern Ethiopia.…”
Section: Husband Involvement In Nutrition Educationmentioning
confidence: 99%
“…Pre eclampsia in 19.5% (n = 88) and placental abruption in 4.6% (n = 21). 17 Though the adverse fetal outcome in developed countries is very low, yet it is higher in babies born to teenage mothers as compared to babies born to mothers in their twenties. In our study regarding fetal outcome, incidence of still birth was found to be 15.38% and low birth weight was observed in 19.6% (20/102), it is similar to a local study that showed 20.04% low birth weight newborn to teenage women.…”
Section: Teenage Pregnancymentioning
confidence: 99%